2020
DOI: 10.3389/fncel.2020.00065
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of Neuroinflammatory Responses Following Intracranial Injection of G-Deleted Rabies Viruses

Abstract: Viral vectors are essential tools for the study of neural circuits, with glycoprotein-deleted rabies viruses being widely used for monosynaptic retrograde tracing to map connectivity between specific cell types in the nervous system. However, the use of rabies virus is limited by the cytotoxicity and the inflammatory responses these viruses trigger. While components of the rabies virus genome contribute to its cytotoxic effects, the function of other neuronal and non-neuronal cells within the vicinity of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 60 publications
(74 reference statements)
4
34
0
Order By: Relevance
“…Collecting the entire transcriptome of injected and non-injected animals offers an opportunity to study the effects of AAV transduction on the host cell transcriptome. A similar investigation has been conducted with G-deleted rabies virus (Huang and Sabatini, 2020). This study demonstrated that virus infection led to the downregulation of genes involved in metabolic processes and 90 neurotransmission in host cells, whereas genes related to cytokine signaling and the adaptive immune system were upregulated.…”
Section: Introductionsupporting
confidence: 58%
“…Collecting the entire transcriptome of injected and non-injected animals offers an opportunity to study the effects of AAV transduction on the host cell transcriptome. A similar investigation has been conducted with G-deleted rabies virus (Huang and Sabatini, 2020). This study demonstrated that virus infection led to the downregulation of genes involved in metabolic processes and 90 neurotransmission in host cells, whereas genes related to cytokine signaling and the adaptive immune system were upregulated.…”
Section: Introductionsupporting
confidence: 58%
“…In a comparative manner, in neurodegenerative diseases, the antibody‐mediated clearance of tau protein by microglia in vitro is dependent on Fc‐gamma receptor binding (Andersson et al , 2019); Fc‐gamma receptor is key to antibody uptake by neurons (Congdon et al , 2013). Consequently, the effective rabies virus clearance by the RVC20/RVC58 mAbs may be reinforced by Fc‐gamma receptor binding, by permitting the access of the mAbs inside infected neurons, and by modulating microglial activity and inflammatory mediators’ production, or even by promoting the infiltration of leukocytes (Quan et al , 2009; Chauhan et al , 2017; Huang & Sabatini, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Vento et al analyzed the transcriptome of about 70,000 single-cells from human first-trimester placentas, and they found three subsets decidual NK cells (dNK1. dNK2, and dNK3) [ 205 ]. These subsets co-express the tissue-resident markers CD49a (ITGA1) and CD9.…”
Section: Uterine Nk Cellsmentioning
confidence: 99%
“…These subsets co-express the tissue-resident markers CD49a (ITGA1) and CD9. dNK1 cells express CD39 (ENTPD1), CYP26A1, and B4GALNT1, whereas the defining markers of dNK2 cells are ANXA1 and ITGB2; dNK3 cells express CD160, KLRB1, and CD103 (ITGAE), but not the innate lymphocyte cell marker CD127 [ 205 ].…”
Section: Uterine Nk Cellsmentioning
confidence: 99%